Evaluation of 3 Months of Once-Weekly Rifapentine and Isoniazid for Latent Tuberculosis Infection. Issue 5 (May 2020) - Walker, Ramara E.; Bass, Stephanie; Srinivas, Pavithra; Miranda, Cyndee; Johnson, Lucileia; Pallotta, Andrea M.
Background: Centers for Disease Control and Prevention recommends 3 months of once-weekly rifapentine/isoniazid (3HP) for latent tuberculosis infection (LTBI) treatment given by directly observed therapy (DOT) or self-administered therapy (SAT) in patients ≥2 years old. 3HP has been associated with increased incidence of hepatic, gastrointestinal, flu-like, and cutaneous adverse drug reactions (ADRs) compared with isoniazid monotherapy.Objective: This study evaluated 3HP completion rates and tolerability for LTBI treatment in a real-world setting.Methods: A single-center retrospective cohort with a nested case-control study, comparing patients experiencing ADRs with those who did not, evaluated patients ≥18 years old receiving 3HP by DOT or SAT for LTBI at Cleveland Clinic from October 2011 through July 2018. Information on baseline characteristics, 3HP administrations, and ADRs were collected.Results: Of 199 patients screened, 144 were included (111 DOT, 33 SAT). 3HP completion rates were high at 82.6% and similar between DOT and SAT groups. During treatment, 92/144 (63.9%) patients experienced any ADR. The most common ADR included flu-like symptoms (38.2%) and gastrointestinal (31.9%) and hepatic (2.1%) reactions. Despite high rate of overall ADRs, rates of significant ADRs (grade 2 or higher) were 4.2%. Overall, 9% of patients discontinued 3HP because of ADRs. After adjusting for other factors associated with ADRs at baseline, SAT was not associated with increased incidence of ADRs, but female sex was a significant predictor (odds ratio = 2.61 [95% CI, 1.23 to 5.56]).Conclusion and Relevance: This study observed high 3HP treatment completion rates, low incidence of significant ADRs, and low discontinuation rates resulting from ADRs.